Madrasah Head Leadership Strategy in Post Coronavirus Disease Pandemic (Covid-19) - Evina, Ita; Mu’in, Juhri Abdul; Syahril, Sulthan; Kesuma, Guntur Cahaya (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study aims to determine the strategy of the Head of the Madrasa after the Covid-19 pandemic. The research method uses a phenomenological qualitative research approach and information data collection techniques research is carried out using interview techniques, observation (observation), and documentation. The instrument used is in the form of a list of interview questions, furthermore, in this research, guaranteeing the reliability of the data obtained is checking the validity of the data, which is carried out based on certain criteria. These criteria are the degree of trust/credibility, transferability, dependency/dependability, and certainty/confirmability. Data analysis in the Miles and Huberman model can go through three main processes, data reduction, data presentation, and conclusion. The research results show a). Environmental Analysis in managing East Lampung MIN after the Covid-19 pandemic, East Lampung MIN analyzed the madrasa's internal and external environment using Swot analysis. Then, madrasas used power strategy, persuasive strategy and normative re-education strategy by involving stakeholders, including the Ministry of Religion, supervisors, madrasa heads, teachers and parents and guardians of students to determine the next work program. b). The formulation of a post-pandemic strategy for East Lampung MIN was formulated or developed a strategy based on the policies of the Ministry of Religion and Permendiknas No. 19 of 2007. It was adjusted to the school's vision, mission and goals that had been prepared according to the East Lampung MIN work plan. c). The implementation of the MIN management strategy after the Covid-19 pandemic, based on the formulation of a strategy prepared according to the East Lampung MIN work plan, was divided into each short, medium and long-term programs. d). Evaluation of the East Lampung MIN management strategy after the Covid-19 pandemic, including direct observation and supervision, e). Strategy-based Management Development. Model character education can be applied to madrasas after the Covid-19 pandemic because it focuses on restoring teacher character and building student character through habituation from the components in the management strategy itself.